Incorporating expert knowledge in farmers’ opportunity cost of supplying environmental services in rural Cameroon - Claudiane Yanick Moukam; Calvin Atewamba (Bio-based and Applied Economics, 2023)
This paper uses a Bayesian approach to incorporate non-data information in the estimate of the opportunity cost of farmers to conserve biodiversity and facilitate carbon sequestration in rural Cameroon. Our field survey reveals that few farmers are willing to participate in environmental protection programs without compensation. As shown by a multidimensional preferences analysis, this behavior may come from the disconnection between environmental values and socioeconomic values. A Bayesian analysis of the Tobit model of the Willingness To Accept compensation (WTA) to participate in agroforestry programs underlines that aging, higher educational attainment, and higher socioeconomic status are very likely to promote pro environmental behaviors. The resulting opportunity cost of supplying environmental services is estimated at 10,775 Fcfa with a standard deviation of 333,6 Fcfa per farmer. These results are qualitatively different from the related literature. They emphasizes the relative importance of accounting for expert knowledge in the interpretation of environmental policies.